Community-Based Waste Management Model in Villages: Turning Organic Waste into Ecological Enzymes - Suhartono Winoto; Asti Novita; M.R. Khairul Muluk; Oscar Radyan Danar (Universitas Sebelas Maret, 2025)
Waste management is one of the important issues in Indonesia, especially in rural areas because it is related to the quality of the environment, public health, and local economic sustainability. This study aims to explore a community-based waste management model in Baosan Lor Village by converting organic waste into environmentally friendly enzymes as an alternative to organic fertilizers and environmental cleaners. This study uses case studies and a qualitative descriptive approach. Data was gathered through field observations and in-depth interviews with representatives of the Karang Taruna youth organization and Gapoktan Wanita. Additionally, documentation of the procedures used to produce environmentally friendly enzymes was used. The study shows how the women's gapoktan contributes significantly to training on environmentally friendly enzyme manufacturing and garbage sorting activities, with active support from the Youth Organization and guidance from the Tourism and Agriculture Office. This concept has achieved two objectives: raising environmental consciousness and generating revenue through the sale of organic fertilizer. However, it faces problems such as limited resources and uneven community involvement. It is possible to develop this concept into an environment-based educational tour as it can offer a long-term solution to the problem of organic waste at the village level.